Kualitas Kualitas Video Pembelajaran Teks Eksplanasi Peristiwa 10 November Elemen Membaca dan Memirsa - Ngatma'in Ngatma'in; Lailatul Irmiah; Sujinah Sujinah; Tining Haryanti; Eko Supriyanto (Universitas Muhammadiyah Kotabumi, 2023)
Abstract: This study aims to describe the quality of the explanatory text learning videos for the events of November 10 based on validity, practicality, and effectiveness. Validity is based on the assessment of material experts and media experts. Practicality based on user assessment and student responses. Effectiveness based on the results of trials in class. This study uses research and development methods. The research model uses ADDIE (Raiser and Mollenda). Data collection instruments use questionnaires and tests. The results of the study show that the learning video of the explanatory text of the events of 10 November has good quality reading and viewing elements. The results of the expert's assessment stated that all aspects of the learning video material were in the very good category (80.68%). The results of the media expert's assessment stated that the learning video design was in the very good category (89.28%). The results of the user assessment stated that all aspects of the learning videos were in the very good category (93%). The results of student responses stated that all aspects of learning videos were in the very good category (83.8%). The trial results stated that all aspects of the learning video were effective and in the very good category (71.42%). Based on data analysis, it can be stated that the learning videos are of high quality and can be used as learning media for explanatory texts on the events of November 10 in class VII-B at SMP Muhammadiyah 17 Surabaya. Keywords: explanatory text, learning video quality Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kualitas video pembelajaran teks eksplanasi peristiwa 10 November berdasarkan kevalidan, kepraktisan, keefektifan. Kevalidan berdasarkan penilaian ahli materi dan ahli media. Kepraktisan berdasarkan penilaian pengguna dan respon peserta didik. Keefektifan berdasarkan hasil uji coba di kelas. Penelitian ini menggunakan metode penelitian dan pengembangan. Model penelitian menggunakan ADDIE (Raiser dan Mollenda). Instrumen pengumpulan data menggunakan angket dan tes. Hasil penelitian menunjukkan video pembelajaran teks eksplanasi peristiwa 10 November elemen membaca dan memirsa berkualitas. Hasil penilaian dari ahli menyatakan bahwa seluruh aspek materi video pembelajaran dalam kategori sangat baik (80,68%). Hasil penilaian dari ahli media menyatakan bahwa desain video pembelajaran dalam kategori sangat baik (89,28%). Hasil penilaian dari pengguna menyatakan bahwa seluruh aspek video pembelajaran dalam kategori sangat baik (93%). Hasil respon peserta didik menyatakan bahwa seluruh aspek video pembelajaran dalam kategori sangat baik (83,8%). Hasil uji coba menyatakan bahwa seluruh aspek video pembelajaran efektif dan dalam kategori sangat baik (71,42%). Berdasarkan analisis data dapat dinyatakan bahwa video pembelajaran berkualitas dan dapat digunakan sebagai media pembelajaran teks eksplanasi peristiwa 10 November di kelas VII-B di SMP Muhammadiyah 17 Surabaya. Kata Kunci: kualitas video pembelajaran, teks eksplanasi